DESIGNING AND IMPLEMENTING THE EDUCATIONAL GAME “INDONESIAN TRIBES” FOR THE KINDERGARTEN STUDENTS - Pikir Wisnu Wijayanto; Yahdi Siradj (Vision: Journal for Language and Foreign Language Learning, 2016)
This study is aimed at describing the educational game “The Indonesian Tribes” as multimedia application in the learning activities for the students in kindergarten. This multimedia application is de- signed to facilitate the students in order to improve their knowledge of tribes and cultures in Indonesia such as the traditional clothes, houses, dances in Indonesia, and the gamelan musical instruments. This application is equipped with a Kinect sensor technology to de- tect the external trigger such as speech and gesture recognition that will further encourage the liveliness; children are play while learning. It is in line with the characteristics of the kindergarten students who love to play and learn in their own imagination. The game is also completed with audio-visual animations in various contents, and interactive nature in terms of  playing and learning activities with a simple description and instruction of the English language. The use of interactive contents in this application enables them to have some senses owned better and more effective, such as the senses of sight, hearing, and motorist functions. Also for teachers, it can increase the teaching creativity and create a good atmosphere of learning. In other words, this educational game can enrich the way children understand the essence of learning through playing.